The analysis of the motor characteristics of D‐RME‐E fuel blend during on‐field tests - Raslavičius, Laurencas; Bazaras, Žilvinas (Transport, 2009)
A detailed analysis of the characteristics of D‐RME‐E (diesel‐rapeseed methyl ester‐ethanol) was carefully performed fuelling an 18 kW capacity tractor unit equipped with the four‐stroke D21A1 diesel engine (combustion chamber consists of a dished piston). The conducted on‐field test demonstrated a positive effect on the dynamic and ecological characteristics of the tractor unit while fuelling the engine with biodiesel blend 70%D+30%RME (hereinafter ‐ B30) admixed with dehydrated ethanol additive (5% (v/v)). This compound did not affect a decrease in the diesel engine power, and in the range of experiment error, showed a tendency of ∼2% fuel economy compared to pure B30. A dramatic decrease in PM (40%), HC (25%) and CO (6%) emissions comparing to fossil diesel was observed when operating the tractor unit at maximum traction power which is a characteristic operating mode of the heavy duty transport means of agricultural purpose. NOx emission of the proposed D‐RME‐E blend showed a tendency to decrease to 4% compared to B30. First published online: 27 Oct 2010